A modern technique to detect potholes by Computer Vision and Deep Learning - Saif, Muntasir Mahmud; Badsha, Tanvir; Khan, Mohammed Arman; Sakib, Sadman; Bin Akbar, Rafeed (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science 2022.